Cognitive-behavioral therapy for treatment-resistant depression in adults and adolescents: a systematic review - Zakhour,Stephanie (2020)
Abstract Objective To conduct a systematic review of literature on use and efficacy of cognitive-behavioral therapy (CBT) for treatment of treatment-resistant depression in adults and adolescents. Methods We performed a systematic review according to the Prisma Guidelines of literature indexed on the PubMed, SciELO, Psychiatry Online, Scopus, PsycArticles, Science Direct and the Journal of Medical Case Reports databases. Randomized controlled trials, open studies and case reports were included in the review. Results The searches returned a total of 1,580 articles, published from 1985 to 2017. After applying the inclusion criteria, 17 articles were selected, their complete texts were read and 8 were included in this review. Four of these studies were randomized controlled trials with adults, one of which covered a post-study follow-up period; two were randomized controlled trials with adolescents, one of which presented follow-up data; one was an open study; and one was a case report. The studies provide good quality and robust evidence on the topic addressed. Conclusions A combination of CBT with pharmacotherapy for treatment-resistant patients shows a decrease in depressive symptoms. CBT can be an effective type of therapy for adults and adolescents with treatment-resistant depression.